Ozoniotherapy: adjuvant therapy in the treatment of knee osteoarthritis (Research, Society and Development, 2022)
Knee osteoarthritis (KOA) is one of the degenerative joint diseases that causes pain, functional impairment and quality of life that is associated with a significant economic impact. Ozone therapy (OT) has been suggested in clinical practice as a promising therapy and adjunct to clinical rehabilitation due to favorable results in the treatment of joint diseases such as KOA. Thus, the purpose of this study is to present, through a narrative review, an understanding of the current evidence available on the clinical importance of including OT in the treatment of KOA. The bibliographic databases of PubMed/MEDLINE, Virtual Health Library (VHL), Web of Science and SciELO were used. Based on peer-reviewed studies, the studies analyzed demonstrate that OT exerts positive effects in reducing the level of pain, improving functionality and quality of life in patients with KOA due to its ability to modulate the joint inflammatory process and act on pathways. endogenous inhibition of pain control. Furthermore, the authors support that OT therapy may be particularly important for patients experiencing adverse drug therapy effects and/or who are not candidates for surgery. Thus, OT can be suggested as an adjuvant method for rehabilitation and effective in the treatment of chronic degenerative inflammatory joint diseases, as it is a minimally invasive method and has relatively low costs. However, it is necessary to carry out controlled and randomized clinical studies in order to elucidate ideal treatment protocols to be used safely in clinical practice.